2008
DOI: 10.1002/hed.20913
|View full text |Cite
|
Sign up to set email alerts
|

Use of combined molecular biomarkers for prediction of clinical outcomes in locally advanced tonsillar cancers treated with chemoradiotherapy alone

Abstract: Background. Environmental exposures to tobacco, alcohol, human papillomavirus (HPV) and/or Epstein-Barr virus (EBV), all of which can perturb multiple cell cycle proteins or tumor suppressors, have been implicated in the pathogenesis of different subsets of head and neck cancers. The aim of this study was to investigate to which extent the virus infection by itself, and/or the altered cell cycle proteins, contributes to prognosis in locally advanced tonsillar squamous cell carcinomas (TSCCs) treated with concu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
0
23
1
Order By: Relevance
“…Very few studies have assessed the prevalence of HPV among oropharyngeal cancer cases in Taiwan. Depending on the methods used, the prevalence of HPV in tonsillar cancer in Taiwan ranged from 13 to 75% . Because these studies are hospital‐based and have a small sample size (sample size ranged from 46 to 111), they may not accurately represent the true HPV prevalence of the tonsillar cancer diagnosed in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have assessed the prevalence of HPV among oropharyngeal cancer cases in Taiwan. Depending on the methods used, the prevalence of HPV in tonsillar cancer in Taiwan ranged from 13 to 75% . Because these studies are hospital‐based and have a small sample size (sample size ranged from 46 to 111), they may not accurately represent the true HPV prevalence of the tonsillar cancer diagnosed in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Several limitations must be considered when interpreting the results of the current study. A major limitation is that the definition of "HPV-related HNC" is based on anatomical [32][33][34] Because these studies are hospital-based and have a small sample size (sample size ranged from 46 to 111), they may not accurately represent the true HPV prevalence of the tonsillar cancer diagnosed in Taiwan. In addition, these studies did not provide information regarding the temporal change in the prevalence of HPV in oropharyngeal cancer.…”
Section: Epidemiologymentioning
confidence: 99%
“…CDKN1A(p21), a tumor suppressor protein in the TP53 cascade, was also strongly associated with favorable patient outcome (15). Fury (2010) similarly found a correlation between CDKN1A(p21) and CDKN2A(p16) positivity in tonsillar squamous cell carcinoma, although two other studies found no association between HPV and CDKN1A(p21) (16, 17, 28). Previous studies have also found CDKN1A(p21) overexpression in cervical carcinomas and intraepithelial neoplasia (CIN), the majority of which were HPV-related lesions, suggesting that CDKN1A(p21) could play a role in HPV-mediated oncogenesis (29, 30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of CDKN1A(p21) expression with HPV and good prognosis in tonsillar squamous cell carcinoma has not been a universal finding (16, 17). …”
Section: Introductionmentioning
confidence: 99%
“…12 Although the prognostic significance of HPV infection for head and neck cancers is not yet certain, recent studies have reported a better prognosis for patients with HPV-positive tumours than those with HPV-negative tumours. Some authors have suggested that the combined biomarkers oncogenic HPV positivity and p53, pRb and p21 tumour suppressor expression may provide prognostic molecular classification superior to that of the TNM staging system for advanced tonsillar squamous cell carcinomas.…”
Section: Figmentioning
confidence: 99%